Excipient knowledgebase: Development of a comprehensive tool for understanding the disposition and interaction potential of common excipients - Savannah J. McFeely; Jingjing Yu; Yan Wang; Cheryl Wu; Isabelle Ragueneau‐Majlessi (Wiley, 2021)
Abstract Although the use of excipients is widespread, a thorough understanding of the drug interaction potential of these compounds remains a frequent topic of current research. Not only can excipients alter the disposition of coformulated drugs, but it is likely that these effects on co‐administered drugs can reach to clinical significance leading to potential adverse effects or loss of efficacy. These risks can be evaluated through use of in silico methods of mechanistic modeling, including approaches, such as population pharmacokinetic (PK) and physiologically‐based PK modeling, which require a comprehensive understanding of the compounds to ensure accurate predictions. We established a knowledgebase of the available compound (or substance) and interaction‐specific parameters with the goal of providing a single source of physiochemical, in vitro, and clinical PK and interaction data of commonly used excipients. To illustrate the utility of this knowledgebase, a model for cremophor EL was developed and used to hypothesize the potential for CYP3A‐ and P‐gp‐based interactions as a proof of concept.